Professional Development, Departmental Contexts, and Use of Instructional Strategies. Issue 4 (19th September 2014) - Lattuca, Lisa R.; Bergom, Inger; Knight, David B.
Abstract Background A report from the American Society for Engineering Education (Jamieson & Lohmann, 2012) identified career‐long professional development for faculty, teacher training in graduate programs, departmental climates that value and support educational innovation, and reward systems that recognize achievements in educational innovation as mechanisms to improve undergraduate engineering education. These factors have long been assumed to influence faculty members' choices to engage in educational improvements, but their relationships with teaching practices rarely have been studied. Purpose We examined the relationships among professional development, departmental contexts, and engineering faculty members' use of student‐centered teaching practices. Design/Method This study drew on a nationally representative survey dataset of 906 engineering faculty members from 31 four‐year institutions. We used multiple regression analyses to investigate whether graduate training, professional development, and institutional factors (e.g., reward systems) relate to engineering faculty members' use of student‐centered teaching practices, such as active learning and frequent and detailed feedback to students. Results Professional development activities and, to a lesser extent, graduate training in teaching positively related to the use of student‐centered teaching practices. We provide some of the first evidence that graduate training in teaching is linked to the use of student‐centered teaching practices. Only modest relationships were observed between departmental environments and teaching practices. Conclusion Engineering departments seeking to increase the use of student‐centered teaching practices should consider supporting faculty engagement in on‐ and off‐campus professional development activities. Supporting these activities may be more effective than emphasizing research on engineering education and curriculum enhancement in reward decisions.